Modeling of multimass systems torsionally deformed with variable inertia. (27th July 2006) - Pielorz Pielorz, Amalia Amalia; Skóra Skóra, Monika Monika
Abstract : Dynamic investigations of multimass discrete-continuous systems having variable moment of inertia are performed. The systems are torsionally deformed and consist of an arbitrary number of elastic elements connected by rigid bodies. The problem is nonlinear and it is linearized after appropriate transformations. It is shown that such problems can be investigated using the wave approach. Some analytical considerations and numerical calculations are done for a two-mass system with a special case of boundary conditions.